Dynamics of the tectonic assembly of northeast Laurentia ingeon 18 (1.9-1.8 Ga) - Hoffman, Paul (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Summary A tectonic model is proposed, based on the Cenozoic evolution of Southeast Asia, in which the southeast arm of the Rae Province rotated clockwise in response to collision alindentation of the Superior Province. A dextralpull-apart basin characterized by mafic sill-sediment complexes formed along the leading edge of the rotating block. Relics of this basin, analogous to the Andaman Sea basin of Southeast Asia, were subsequently thrust onto the Superior Province margin where they occur as allocations in the Labrador Trough.A wedge-shaped ancestral Baffin basin, analogous to the South China Sea, opened simultaneously in the wake of the rotating block.The margins of this basin are delineated bythe Foxe-Rlnkian and Dorset fold belts; their convergence and disappearance westward reflect the primary shape of the basin. North-west-dipping subduction beneath the mouth of the basin accommodated convergence of the Burwell and Nain provinces from the southeast and gave rise to the Cumberland batholith. Docking of the Burwell and Nain provinces caused compressional collapse ofthe ancestral Baffin basin and sinistral transpression of the Torngat Orogen, respectively.The model is well constrained by existing U-Pb geochronological data and makes predictions which can be tested by additional data.